Porous cloth for gas diffusion layer of fuel cell, fuel cell and preparation method
The graphene oxide porous cloth, prepared by shearing and graphitization, addresses the brittleness and cost issues of carbon fiber-based gas diffusion layers, providing improved conductivity and flexibility for fuel cells.
Patent Information
- Application Number
- CN202310793626.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
Existing fuel cell gas diffusion layers made from carbon fiber materials are brittle, costly, and suffer from poor conductivity, making them prone to damage and reducing the service life of fuel cells.
A method involving the preparation of a graphene oxide porous cloth through shearing, fusion, low-medium temperature reduction, and graphitization to create a flexible and conductive gas diffusion layer.
The resulting graphene porous cloth offers high conductivity, flexibility, and lower production costs, enhancing the performance and durability of fuel cells.
Smart Images

Figure BDA0004314277960000161 
Figure HDA0004314277970000011 
Figure HDA0004314277970000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell materials, and in particular to a porous cloth for a fuel cell gas diffusion layer, a fuel cell and a preparation method thereof. Background Art
[0002] The gas diffusion layer is basically formed by conductive porous materials, so as to achieve the functions of supporting the catalyst layer, collecting current, transmitting gas and repelling water, and finally realize the redistribution of the reaction gas and the water of the reaction product between the bipolar plate and the catalyst layer. The base layer usually uses porous carbon fiber paper, carbon fiber cloth, etc., which mainly plays the role of supporting the microporous layer and the catalyst layer. The microporous layer is usually a layer made on the surface of the base layer to improve the pore structure of the base layer. Its main function is to reduce the contact resistance between the catalyst layer and the base layer, so as to redistribute the gas and water, prevent the electrode catalyst layer from being "flooded", and prevent the catalyst layer from leaking into the base layer during the preparation process.
[0003] Usually, the diffusion layer of fuel cells is mostly made of carbon cloth prepared by compounding carbon fiber, polymer fiber and adhesive, and then further carbonized at a high temperature above 1600℃; the main manufacturers are Toray of Japan, SGL of Germany and Ballard of Canada. The technology for preparing carbon paper is complicated, and there is secondary high-temperature carbonization, which is brittle and easy to be damaged during the preparation of membrane electrode composite, as well as poor conductivity and high cost. In addition, it is easy to be damaged during the operation of the fuel cell in the later stage, which affects the operation of the catalyst layer and reduces the service life of the fuel cell.
[0004] In the prior art, in the Chinese patent with the announcement number CN109698361A, it is proposed to adhere graphene and new carbon materials to porous inorganic powders to form large-particle composite carbon particles through urea plasticized gelatinized starch and polyvinyl alcohol, and then extrude and granulate with carbon fiber, inorganic fiber, wood fiber, thermoplastic polymer, polytetrafluoroethylene powder, soluble salt, and lubricant; micro-foaming by a film forming machine to form a graphene carbon film prototype sheet; after roller traction and stretching, while the temperature of three groups of traction rollers gradually increases, part of polyvinyl alcohol and gelatinized starch decompose and carbonize to form micropores, and polytetrafluoroethylene powder micro-melts as a bonding proppant to ensure the strength and flexibility of the sheet, and further elute the soluble salt to form micropores to obtain a flexible graphene carbon film. The graphene carbon film obtained by this method has excellent air permeability, conductivity, and flexibility, and the preparation process is easy to control and easy to scale continuous production. However, the graphene carbon film has only been carbonized but not graphitized, and its conductivity is slightly poor. In addition, the Chinese patent with patent publication number CN103556543A also discloses that short-cut carbon fiber, plant fiber, thermal bonding fiber and carbon black are used as raw materials, and paper is made by wet papermaking process after decomposition, pulping and slurrying, and then coated with waterproof coating. The proportion of each raw material is as follows in parts by weight: 65-75 parts of short-cut carbon fiber, 10-15 parts of plant fiber, 10-15 parts of thermal bonding fiber and 0-10 parts of carbon black. Although the patent adopts a production process combining wet forming, hot pressing and coating, it has the characteristics of simple process flow, easy control of product quality, environmental protection of production process, etc., but it still uses carbon fiber, plant fiber, thermal bonding fiber, etc., so that the high-performance carbon paper specially used for fuel cell gas diffusion layer still has the above-mentioned disadvantages. Therefore, the present invention proposes a porous cloth for fuel cell gas diffusion layer, a fuel cell and a preparation method to at least partially solve the problems that may exist in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a porous cloth for a fuel cell gas diffusion layer, a fuel cell and a preparation method, which can propose solutions to the deficiencies of the prior art and solve the problems of the fuel cell gas diffusion layer in the prior art, such as high brittleness, easy damage during the preparation of the membrane electrode composite, poor electrical conductivity, high cost, etc., and can have the advantages of good flexibility and electrical conductivity, as well as low cost.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] A method for preparing a porous cloth for a fuel cell gas diffusion layer, comprising:
[0008] Shearing the graphene oxide film according to predetermined requirements to obtain graphene oxide film filaments, and shearing the graphene oxide film filaments to obtain graphene oxide short filaments;
[0009] fusing and assembling the graphene oxide membrane filaments and the graphene oxide short filaments to obtain a graphene oxide porous cloth;
[0010] The graphene oxide porous cloth is subjected to low-medium temperature reduction to obtain a semi-finished graphene porous cloth; wherein the temperature range of the low-medium temperature environment includes a first stage of low temperature of 60°C-120°C, a second stage of medium temperature of 300°C-1600°C, and a reduction time of 6h-96h;
[0011] Graphitizing the semi-finished graphene porous cloth to obtain a density of 0.1 g / cm 3 -0.8g / cm 3 , a graphene porous cloth with a porosity of 50%-90% and a thickness of 100μm-5000μm, wherein the temperature of the high temperature environment is 2000℃-3500℃, the heating rate is 1℃ / min-20℃ / min, and the insulation time is 30min-360min.
[0012] Further, in the present invention, the above-mentioned step of shearing the graphene oxide film according to predetermined requirements to obtain the graphene oxide film filaments, and shearing the graphene oxide film filaments to obtain the graphene oxide short filaments, comprises:
[0013] The graphene oxide is made into a graphene oxide film with a thickness of mainly 30-500 μm;
[0014] The graphene oxide film is physically cut into graphene oxide film filaments with a width of 10 μm-1000 μm and a length of 5 cm-5000 cm;
[0015] At least a portion of the graphene oxide membrane filaments are cut into graphene oxide short filaments with a length of 0.5 cm-5 cm.
[0016] Further, in the present invention, the above-mentioned fusion assembly of the graphene oxide membrane filaments and the graphene oxide short filaments to obtain the graphene oxide porous cloth comprises:
[0017] Dispersing the graphene oxide membrane filaments and the graphene oxide short filaments in a mixture of alcohol and water in a volume ratio of 1:0.25-10;
[0018] The graphene oxide membrane filaments and the graphene oxide short filaments in the mixed solution are overlapped in an orderly and / or disorderly manner by filtration or coating to form a graphene oxide porous cloth with an arbitrary shape and a pore size of 0.5 μm-100 μm.
[0019] Furthermore, in the present invention, the above-mentioned graphene oxide porous cloth is subjected to low-medium temperature reduction to obtain a semi-finished graphene porous cloth, comprising:
[0020] The graphene oxide porous cloth is chemically reduced in a hydrazine hydrate solution with a concentration of 0.5% to 90% or hydrazine hydrate vapor with a concentration of 50% to 95%, or in an environment where it is immersed in an aqueous sodium ascorbate solution with a mass fraction of 1% to 50%, or an aqueous hydrobromic acid solution with a mass fraction of 1% to 48%, or an aqueous hydroiodic acid solution with a mass fraction of 1% to 58%, with the ambient temperature maintained at 60° C. to 95° C., wherein the reduction time is 2 h to 48 h;
[0021] The reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 300° C. to 1600° C. to remove waste gas, thereby obtaining a semi-finished graphene porous cloth.
[0022] Further, in the present invention, the reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 300° C. to 1600° C. to remove waste gas, thereby obtaining a semi-finished graphene porous cloth, comprising:
[0023] The graphene oxide porous cloth is chemically reduced in a hydrazine hydrate solution with a concentration of 0.5% to 90% or hydrazine hydrate vapor with a concentration of 50% to 95%, or in an environment where it is immersed in an aqueous sodium ascorbate solution with a mass fraction of 1% to 50%, or an aqueous hydrobromic acid solution with a mass fraction of 1% to 48%, or an aqueous hydroiodic acid solution with a mass fraction of 1% to 58%, with the ambient temperature maintained at 60° C. to 95° C., wherein the reduction time is 2 h to 48 h;
[0024] The reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 600° C. to 1600° C. to remove waste gas, thereby obtaining a semi-finished graphene porous cloth.
[0025] Further, in the present invention, the reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 300° C. to 1600° C. to remove waste gas to obtain the graphene porous cloth, comprising:
[0026] The reduced graphene porous cloth is treated in argon or nitrogen at a medium temperature environment of 600° C. to 1600° C. to remove waste gas, thereby obtaining the graphene porous cloth.
[0027] Further, in the present invention, the semi-finished graphene porous cloth is graphitized to obtain a graphene porous cloth having a density of 0.1 g / cm3-0.8 g / cm3, a porosity of 50%-90%, and a thickness of 100 μm-5000 μm, and further comprising:
[0028] The graphene porous cloth is subjected to calendering treatment to obtain a flexible graphene porous cloth with a thickness of 10 μm-100 μm or 100 μm-500 μm, a density of 0.2 g / cm3-1 mg / cm3, and a porosity of 50%-90%.
[0029] Further, in the present invention, the above-mentioned graphene porous cloth is subjected to calendering treatment to obtain a flexible graphene porous cloth having a thickness of 10 μm-100 μm or 100 μm-500 μm, a density of 0.2 g / cm3-1 mg / cm3, and a porosity of 50%-90%, comprising:
[0030] The graphene porous cloth is subjected to static pressure treatment to obtain the flexible graphene porous cloth; wherein the static pressure includes segmented and graded static pressure, the pressure is 100 kPa-40 MPa and the static pressure time is 30 min-1440 min;
[0031] or,
[0032] The graphene porous cloth is subjected to rolling treatment to obtain the flexible graphene porous cloth, wherein the rolling pressure is 100 kPa-20 MPa, and the rolling speed is 0.1 m / min-5 m / min;
[0033] or,
[0034] The graphene porous cloth is subjected to static pressure treatment, wherein the static pressure includes segmented and graded static pressure, the pressure is 100 kPa-40 MPa and the static pressure time is 30 min-1440 min;
[0035] The porous cloth after static pressing is rolled to obtain the flexible graphene porous cloth, wherein the rolling pressure is 100 kPa-20 MPa, and the rolling speed is 0.1 m / min-5 m / min.
[0036] Furthermore, in the present invention, the calendering treatment of the graphene porous cloth to obtain the flexible graphene porous cloth may also include:
[0037] The graphene porous cloth is rolled by a double-roller machine to obtain the flexible graphene porous cloth with a thickness of 100 μm-500 μm, a density of 0.4 g / cm3-0.1 g / cm3, and a porosity of 60%-80%.
[0038] A porous cloth for a fuel cell gas diffusion layer is prepared by the above-mentioned preparation method.
[0039] A fuel cell comprises a porous cloth for a fuel cell gas diffusion layer, which is applied to the fuel cell as a gas diffusion layer; the porous cloth for a fuel cell gas diffusion layer is prepared by the above preparation method.
[0040] The present invention has at least the following advantages or beneficial effects:
[0041] The graphene oxide membrane is cut according to predetermined requirements to obtain graphene oxide membrane filaments, and the graphene oxide membrane filaments are cut to obtain graphene oxide short filaments; the graphene oxide membrane filaments and the graphene oxide short filaments are fused and assembled to obtain graphene oxide porous cloth; the graphene oxide porous cloth is subjected to low-medium temperature reduction to obtain semi-finished graphene porous cloth; the semi-finished graphene porous cloth is graphitized to obtain graphene porous cloth. Compared with the fuel cell gas diffusion layer prepared by traditional carbon fiber, the cost is lower, and its conductivity will also increase. The final fuel cell open circuit voltage finally forms a highly conductive, hydrophobic, uniformly porous and flexible porous cloth for fuel cell gas diffusion layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0043] Figure 1 A flowchart of a method for preparing a porous cloth for a fuel cell gas diffusion layer according to an embodiment of the present invention;
[0044] Figure 2 The front side of the porous cloth for the gas diffusion layer of a fuel cell provided by one embodiment of the present invention (a) is a scanning electron microscope image at different magnifications;
[0045] Figure 3 The reverse side (b) of the porous cloth for the gas diffusion layer of the fuel cell of the present invention is a scanning electron microscope image under different magnification conditions;
[0046] Figure 4 It is a comparison diagram of battery voltage under different current density conditions in two embodiments of the present invention. DETAILED DESCRIPTION
[0047] In order to make the objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] Please refer to Figure 1 , showing a flowchart of a method for preparing a porous cloth for a fuel cell gas diffusion layer according to this embodiment, which comprises the following steps:
[0050] Step S101, cutting the graphene oxide film according to predetermined requirements to obtain graphene oxide film filaments, and cutting the graphene oxide film filaments to obtain graphene oxide short filaments;
[0051] Step S102, fusing and assembling the graphene oxide membrane filaments and the graphene oxide short filaments to obtain a graphene oxide porous cloth;
[0052] Step S103, reducing the graphene oxide porous cloth at low to medium temperature to obtain a semi-finished graphene porous cloth;
[0053] Step S104, graphitizing the semi-finished graphene porous cloth to obtain a graphene porous cloth with a density of 0.1 g / cm3-0.8 g / cm3, a porosity of 50%-90%, and a thickness of 100 μm-5000 μm.
[0054] The graphene porous cloth prepared by the above-mentioned method for preparing the porous cloth for fuel cell gas diffusion layer has lower cost than the fuel cell gas diffusion layer prepared by traditional carbon fiber, and its conductivity will also be increased. The final fuel cell open circuit voltage finally forms a porous cloth for fuel cell gas diffusion layer with high conductivity, hydrophobicity, uniform porosity and excellent flexibility.
[0055] The cost of using graphene oxide membrane filaments as raw materials to make a fuel cell gas diffusion layer skeleton is very low. The material cost can be controlled at 600-2000 yuan / kg, which is more than 50% lower than the cost of using carbon fiber to make a fuel cell skeleton. The graphene oxide porous cloth assembled by fusing the graphene oxide membrane filaments and the graphene oxide short filaments is first subjected to a chemical reduction carbonization treatment, and then subjected to a high-temperature graphitization treatment, so that it has good electrical conductivity and air permeability, and can increase the open circuit voltage of the fuel cell and increase the current density. The present invention provides a path forward for promoting the industrialization of high-performance and low-cost fuel cells.
[0056] As a preferred implementation, the specific process of the above step S101 "cutting the graphene oxide film according to predetermined requirements to obtain the graphene oxide film filaments, and cutting the graphene oxide film filaments to obtain the graphene oxide short filaments" includes: making the graphene oxide into a graphene oxide film with a thickness of mainly 30-500 μm;
[0057] The graphene oxide film is physically cut into graphene oxide film filaments with a width of 10 μm-1000 μm and a length of 5 cm-5000 cm; wherein the physical cutting includes laser cutting, slitting machine cutting, wire cutting and microchannel cutting;
[0058] At least a portion of the graphene oxide membrane filaments are cut into graphene oxide short filaments with a length of 0.5 cm-5 cm.
[0059] It should be noted that laser cutting can achieve high-quality and high-efficiency cutting by focusing the laser beam for local heating and controlling the cutting parameters. It has the advantages of high precision, smooth cutting surface, no cutting edge movement and material loss. Moreover, for brittle materials such as graphene oxide, laser cutting will not cause problems such as cracking or burrs during mechanical cutting. The above-mentioned microchannel cutting can achieve micron-level processing accuracy without causing damage and residue problems. The above-mentioned wire cutting can also achieve high-precision and high-efficiency processing for the cutting of flat thin materials such as graphene oxide films.
[0060] As a preferred implementation, the specific process of "fusion assembling the graphene oxide membrane filaments and the graphene oxide short filaments to obtain the graphene oxide porous cloth" as described in the above step S102 includes dispersing the graphene oxide membrane filaments and the graphene oxide short filaments in a mixture of alcohol and water in a volume ratio of 1:0.25-10;
[0061] The graphene oxide membrane filaments and the graphene oxide short filaments in the mixed solution are overlapped in an orderly and / or disorderly manner by filtration or coating to form a graphene oxide porous cloth with an arbitrary shape and a pore size of 0.5 μm-100 μm.
[0062] As an example, the graphene oxide dispersion is subjected to a coagulation bath to form long fibers and short fibers, and the long fibers and the short fibers are overlapped in an orderly manner and / or disorderly to form a porous graphene oxide cloth. For example, the short fibers can be overlapped in an orderly manner by orderly weaving through a weaving tool, and / or the short fibers can be overlapped in a disorderly manner by filtration or coating to form a porous graphene oxide cloth of any shape with a pore size of 0.5μm-100μm.
[0063] As a preferred implementation manner, in the specific process of "reducing the graphene oxide porous cloth at low or medium temperature to obtain the graphene porous cloth" as described in the above step S103, the graphene oxide porous cloth is placed in a heating device for carbonization reduction treatment, and the reduction temperature can be controlled at 60°C-120°C, and in an inert gas (argon, nitrogen, etc.) environment, the temperature is maintained at 300°C-1600°C for treatment to remove waste gas; wherein the above-mentioned heating device may include a heat source for a reaction chamber, an oven, etc., and an oven may be preferably used in this application, and the heating rate of the heating temperature is 1°C / min-5°C / min, and the reduction time is 6h-96h.
[0064] As a preferred embodiment, the specific process of "graphitizing the graphene porous cloth to obtain a graphene porous cloth with a density of 0.1g / cm3-0.8g / cm3, a porosity of 50%-90%, and a thickness of 100μm-5000μm" as described in the above step S104 includes placing the oxidized graphene porous cloth after carbonization reduction treatment into a heating device such as an oven, and performing graphitization treatment in a high temperature environment to obtain a graphitized porous cloth, wherein the temperature of the high temperature environment is 2000℃-3000℃ or 3000℃-3300℃ or 3300℃-3500℃; the heating rate is 1℃ / min-2℃ / min or 2℃ / min-5℃ / min or 5℃ / min-10℃ / min or 10℃ / min-15℃ / min or 15℃ / min n-20℃ / min, the insulation time is 30min-120min or 120min-360min.
[0065] As a preferred embodiment, the method further comprises: performing a calendering process on the graphene porous cloth to obtain a flexible graphene porous cloth, wherein the thickness of the flexible graphene porous cloth is 10 μm-100 μm or 100 μm-500 μm, and the density is 0.2 g / cm 3 -1mg / cm 3 The calendering treatment includes static pressing the graphene porous cloth to obtain the flexible graphene porous cloth; wherein the static pressing includes segmented and graded static pressing, the pressure is 100kPa-40MPa and the static pressing time is 30min-1440min.
[0066] In a specific embodiment, a graphene oxide membrane with a thickness of 30 μm is cut into membrane filaments by laser cutting, and the length of the membrane filaments is 300 mm and the width is 5 μm;
[0067] Then cut the membrane filament into a length of 0.5 cm;
[0068] The graphene oxide membrane was mixed in a water and alcohol solution, wherein the ratio of water to alcohol was 1:4 (volume ratio), and then filtered to form a circular graphene oxide membrane porous cloth with a pore size controlled to be 0.5 μm;
[0069] The graphene oxide membrane porous cloth formed by filtration was placed in an oven, and the heating rate was controlled at 1°C / min, wherein the middle temperature was 1600°C and kept warm for 30 minutes; the upper middle temperature was kept at 1600°C, which could make it have a better and faster carbonization reduction effect;
[0070] The carbonized graphene oxide porous cloth was subjected to high temperature graphitization, and the heating rate was controlled at 1°C / min, wherein the temperature was 3000°C and kept at this temperature for 30min;
[0071] The graphitized graphene porous cloth is subjected to static pressure, the static pressure is 1000KPa, and the static pressure time is 30min. The final porous cloth for fuel cell gas diffusion layer has a density of 0.2g / cm 3 , thickness is 300μm and porosity is 90%.
[0072] Through testing, the fuel cell gas diffusion layer formed has a vertical thermal resistance of 75mΩ*cm, a horizontal thermal conductivity of a single membrane fiber of 260W / (m*k), and an air permeability of 2500ml·mm / (cm 2 ·hr·mmAq).
[0073] It should be noted that the finished porous cloth formed by high-temperature graphitization can be used in batteries, but in order to make it more uniform and better control its thickness, it is preferred in this application to calender the finished porous cloth, which can also improve its flexibility.
[0074] Example 2
[0075] This embodiment provides a method for preparing a porous cloth for a fuel cell gas diffusion layer, which comprises the following steps:
[0076] Shearing the graphene oxide film according to predetermined requirements to obtain graphene oxide film filaments, and shearing the graphene oxide film filaments to obtain graphene oxide short filaments;
[0077] The graphene oxide membrane filaments and the graphene oxide short filaments are dissolved by a solvent to form a graphene oxide dispersion, wherein the concentration of the graphene oxide is 2 mg / ml-20 mg / ml;
[0078] Forming a porous graphene oxide cloth by orderly overlapping or disorderly overlapping the graphene oxide dispersion;
[0079] The graphene oxide porous cloth is chemically reduced by a chemical reagent in an environment maintained at 60° C.-95° C., and the reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 300° C.-1600° C. to remove waste gas, thereby obtaining a graphene porous cloth, wherein the reduction time is 2 h-48 h;
[0080] The carbonized and reduced graphene oxide porous cloth is subjected to graphitization treatment in a high temperature environment to obtain a graphene porous cloth;
[0081] The method further comprises: performing a calendering treatment on the graphene porous cloth to obtain a flexible graphene porous cloth, wherein the thickness of the flexible graphene porous cloth is 10 μm-100 μm or 100 μm-500 μm, and the density is 0.2 g / cm 3 -1mg / cm 3 , the porosity is 50%-90%.
[0082] As a preferred embodiment, the graphene oxide membrane filaments and the graphene oxide short filaments are fused and assembled to obtain a graphene oxide porous cloth. The graphene oxide dispersion is subjected to a coagulation bath to form long fibers and short fibers, and the long fibers and the short fibers are overlapped in an orderly and / or disordered manner to form a graphene oxide porous cloth.
[0083] As a preferred embodiment, the method of subjecting the graphene oxide porous cloth to low-medium temperature reduction to obtain a semi-finished graphene porous cloth comprises: subjecting the graphene oxide porous cloth to chemical reduction in a hydrazine hydrate solution with a concentration of 0.5%-90% or hydrazine hydrate vapor with a concentration of 50%-95%, or in an environment where the graphene oxide porous cloth is immersed in an aqueous solution of sodium ascorbate with a mass fraction of 1%-50%, or an aqueous solution of hydrobromic acid with a mass fraction of 1%-48%, or an aqueous solution of hydroiodic acid with a mass fraction of 1%-58%, and the ambient temperature is maintained at 60°C-95°C, wherein the reduction time is 2h-48h;
[0084] The reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 600°C-1600°C to remove waste gas, thereby obtaining a graphene porous cloth.
[0085] The graphene oxide porous cloth after carbonization reduction treatment is placed in a heating device and graphitized in a high temperature environment of 3000°C-3500°C to obtain a graphene porous cloth; the heating rate of the high temperature environment is 1°C / min-10°C / min or 10°C / min-15°C / min; the insulation time is 30min-120min or 120min-360min.
[0086] As a preferred implementation manner, the graphene porous cloth is subjected to calendering treatment to obtain a flexible graphene porous cloth, wherein the graphene porous cloth can be subjected to rolling treatment to obtain the flexible graphene porous cloth, wherein the rolling pressure is 100kPa-20MPa, and the rolling speed is 0.1m / min-5m / min; or, the graphene porous cloth is subjected to static pressing treatment, wherein the static pressing includes segmented and graded static pressing, and the pressure is 100kPa-40MPa and the static pressing time is 30min-1440min; the porous cloth after static pressing is rolled to obtain the flexible graphene porous cloth, wherein the rolling pressure is 100kPa-20MPa, and the rolling speed is 0.1m / min-5m / min.
[0087] As an example, the graphene porous cloth can also be rolled by a rolling machine to obtain the flexible graphene porous cloth, wherein the thickness of the flexible graphene porous cloth obtained in this way is 10 μm-100 μm or 100 μm-500 μm, and its density is 0.2 g / cm 3 -1mg / cm 3 , the porosity is 50%-90%; in this example, the flexible graphene porous cloth preferably has a thickness of 100 μm-500 μm and a density of 0.4 g / cm 3 -0.1g / cm 3 , the porosity is 60%-80%.
[0088] In a specific embodiment, a graphene oxide membrane with a thickness of 500 μm is cut into membrane filaments by laser cutting, and the length of the membrane filaments is 300 mm and the width is 50 μm;
[0089] Then cut the membrane thread into a length of 5 cm;
[0090] The graphene oxide membrane was mixed in a water and alcohol solution, wherein the ratio of water to alcohol was 1:1 (volume ratio), and then filtered to form a circular graphene oxide membrane porous cloth with a pore size controlled to be 5 μm;
[0091] The graphene oxide membrane porous cloth formed by filtration was placed in an oven, the heating rate was controlled at 10°C / min, and the temperature was kept at 1600°C for 360 minutes;
[0092] The carbonized graphene oxide porous cloth was subjected to high-temperature graphitization, with the heating rate controlled at 10°C / min, and the temperature was kept at 3300°C for 30 minutes;
[0093] The graphitized graphene porous cloth is rolled on a roller machine with a roller pressure of 20 MPa and a roller speed of 5 m / min. The final porous cloth for fuel cell gas diffusion layer has a density of 0.5 g / cm3, a thickness of 200 μm, and a porosity of 60%.
[0094] Through testing, the fuel cell gas diffusion layer formed has a vertical thermal resistance of 60mΩ*cm, a horizontal thermal conductivity of a single membrane fiber of 560W / (m*k), and an air permeability of 2000ml·mm / (cm 2 ·hr·mmA q).
[0095] Example 3
[0096] A method for preparing a porous cloth for a fuel cell gas diffusion layer, comprising: preparing graphene oxide with a thickness of 30-500 μm and a surface load of 5-50 mg / cm 2 The graphene oxide film; the graphene oxide film is physically cut into the membrane filaments, wherein the physical cutting includes laser cutting, slitting machine cutting, wire cutting and microchannel cutting; at least part of the membrane filaments are continuously sheared to obtain the short filaments; the graphene oxide membrane filaments and the graphene oxide short filaments are dissolved by a solvent to form a graphene oxide dispersion, wherein the concentration of graphene oxide is 2mg / ml-20mg / ml; the graphene oxide dispersion is overlapped in an orderly manner or in an unordered manner to form a graphene oxide porous cloth; the graphene oxide porous cloth is carbonized and reduced in a preset medium temperature environment; wherein the temperature range of the low and medium temperature environment includes a first section of low temperature of 60°C-95°C and a second section of medium temperature of 300°C-2000°C; the carbonized and reduced graphene oxide porous cloth is graphitized in a high temperature environment to obtain a graphene porous cloth;
[0097] The method further comprises: performing a calendering treatment on the graphene porous cloth to obtain a flexible graphene porous cloth, wherein the thickness of the flexible graphene porous cloth is 10 μm-100 μm or 100 μm-500 μm, and the density is 0.2 g / cm 3 -1mg / cm 3 , the porosity is 50%-90%.
[0098] As a preferred implementation, the graphene oxide dispersion can also be formed into a graphene oxide porous cloth of any shape and a pore size of 0.5 μm-100 μm by a random overlapping method, wherein the random overlapping method includes filtration and coating.
[0099] As a preferred embodiment, the graphene porous cloth is subjected to a calendering process, including rolling the graphene porous cloth through a rolling machine to obtain the flexible graphene porous cloth, wherein the thickness of the flexible graphene porous cloth is 100 μm-500 μm and the density is 0.4 g / cm 3 -0.1g / cm 3 , Porosity 50%-80%
[0100] In a specific embodiment, a graphene oxide membrane with a thickness of 500 μm is cut into membrane filaments by laser cutting, and the length of the membrane filaments is 300 mm and the width is 10 μm;
[0101] Then cut the membrane thread into a length of 2 cm;
[0102] The graphene oxide membrane was mixed in a water and alcohol solution, wherein the ratio of water to alcohol was 4:1 (volume ratio), and then filtered to form a circular graphene oxide membrane porous cloth with a pore size controlled to be 10 μm;
[0103] The graphene oxide membrane porous cloth formed by filtration was placed in an oven, the heating rate was controlled at 5°C / min, and the temperature was kept at 1000°C for 300min;
[0104] The carbonized graphene oxide porous cloth was subjected to high temperature graphitization, and the heating rate was controlled at 10°C / min, wherein the temperature was kept at 3200°C for 60min;
[0105] The graphitized graphene porous cloth is rolled on a roller machine with a roller pressure of 10 MPa and a roller speed of 0.1 m / min. The final porous cloth for fuel cell gas diffusion layer has a density of 0.1 g / cm 3 , thickness is 100 μm and porosity is 50%.
[0106] In this embodiment, Figure 2-3 As shown, the porous cloth for fuel cell gas diffusion layer has the following characteristics: Figure 2 and Figure 3 The surface morphology shown in the figure is that the top is in the shape of membrane filaments, and the bottom is almost in the shape of membrane holes, similar to the surface of graphene membrane. When connected together, they all have a certain porosity. Through testing, the fuel cell gas diffusion layer formed has a vertical thermal resistance of 50mΩ*cm, a horizontal thermal conductivity of a single membrane filament of 780W / (m*k), and an air permeability of 1500ml·mm / (cm 2 ·hr·mmAq).
[0107] Example 4
[0108] In the comparison example, the specific implementation method is basically the same as that of the above-mentioned embodiment 3, except that the graphitization process is removed, and the other parts are basically the same; the details are as follows:
[0109] The graphene oxide membrane with a thickness of 500 μm was cut into membrane filaments by laser cutting. The length of the membrane filaments was 300 mm and the width was 10 μm.
[0110] Then cut the membrane thread into a length of 2 cm;
[0111] The graphene oxide membrane was mixed in a water and alcohol solution, wherein the (volume) ratio of water to alcohol was 4:1, and then filtered to form a circular graphene oxide membrane porous cloth with a pore size controlled to be 10 μm;
[0112] The graphene oxide membrane porous cloth formed by filtration was placed in an oven, the heating rate was controlled at 5°C / min, and the temperature was kept at 1000°C for 300min;
[0113] The carbonized graphene porous cloth is rolled on a roller machine with a roller pressure of 10 MPa and a roller speed of 0.1 m / min. The final porous cloth for fuel cell gas diffusion layer has a density of 0.1 g / cm 3 , thickness is 100 μm, porosity is 50%;
[0114] Through testing, the formed fuel cell gas diffusion layer has a vertical resistivity of 150mΩ*cm, a horizontal thermal conductivity of a single membrane fiber of 157W / (m*k), and an air permeability of 1500ml·mm / (cm2·hr·mm Aq).
[0115] By comparing the scheme of Example 3 with the scheme of Example 4, the graphitization step can significantly reduce the vertical resistivity, which can be reduced by more than 50%, and its thermal conductivity can be increased by 4-6 times. Figure 4 As shown, the fuel cell gas diffusion layer of the solution of Example 3 and Example 4 are installed in the same fuel cell monomer to test the electrical performance data. Under the same current density conditions, the open circuit voltage of the fuel cell can be increased by about 0.05V.
[0116] In addition, as shown in Table 1, there is a comparison table of thermal conductivity and cost of original asphalt-based carbon fibers from different manufacturers and graphene membrane fibers of different schemes of the present invention. By comparison, the thermal conductivity of the graphene membrane fibers finally formed in the present invention is not much different from that of traditional carbon fibers, and the cost is 5-10 times lower than that of traditional asphalt-based carbon fibers, thereby being able to prepare a fuel cell gas diffusion layer with low cost and superior performance.
[0117] Table 1
[0118]
[0119] Table 1 is a comparison of the thermal conductivity and selling price of the porous cloth for fuel cell gas diffusion layer made by the solution of the present invention and fiber substrates of some manufacturers.
[0120] It can be seen from the data in Table 1 that the porous cloth for fuel cell gas diffusion layer prepared by the solution of the present application has greatly improved conductivity compared with the solution of the prior art, and the price is significantly lower than the existing price. As a material for fuel cells, it can greatly improve the performance of the battery and reduce the cost of the battery; it has great advantages in both price and parameters and has good market prospects.
[0121] Example 5
[0122] This embodiment provides a porous cloth for a fuel cell gas diffusion layer, which is prepared by the above-mentioned preparation method. The thickness is 0.01mm-5mm, 0.1g / cm3-1.g / cm3, and the porosity is 50%-90%. In this application, the preferred thickness of the porous cloth for a fuel cell gas diffusion layer is 0.01mm-0.5mm; 0.4g / cm3-0.8mg / cm3, and the porosity is 60%-80%.
[0123] Example 6
[0124] This embodiment provides a fuel cell, comprising the above-mentioned porous cloth for fuel cell gas diffusion layer, applied to the fuel cell as a gas diffusion layer; the porous cloth for fuel cell gas diffusion layer; prepared by the above-mentioned preparation method. The vertical thermal resistance of the gas diffusion layer is preferably 50mΩ*cm-150mΩ*cm, the horizontal thermal conductivity of a single membrane fiber is preferably 780W / (m*k)-157W / (m*k), and the air permeability is preferably 1500ml·mm / (cm 2 ·hr·mmAq)-2500ml·mm / (cm 2 ·hr·mmAq).
[0125] The present invention uses graphene oxide membrane silk as the fuel cell gas diffusion layer skeleton, and its cost is very low, which can be controlled at 600-2000 yuan / kg, which is more than 50% lower than the cost of carbon fiber as the fuel cell skeleton. After high temperature treatment, its conductivity and air permeability are relatively good, which can increase the open circuit voltage and current density of the fuel cell. The present invention provides a path forward for promoting the industrialization of high-performance and low-cost fuel cells.
[0126] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0127] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0128] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0129] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.
[0130] The porous cloth for a fuel cell gas diffusion layer, a fuel cell and a preparation method provided by the present invention are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a porous cloth for a fuel cell gas diffusion layer, characterized in that: include: Shearing the graphene oxide film according to predetermined requirements to obtain graphene oxide film filaments, and shearing the graphene oxide film filaments to obtain graphene oxide short filaments; fusing and assembling the graphene oxide membrane filaments and the graphene oxide short filaments to obtain a graphene oxide porous cloth; The graphene oxide porous cloth is subjected to low-medium temperature reduction to obtain a semi-finished graphene porous cloth; wherein the temperature range of the low-medium temperature environment includes a first stage of low temperature of 60°C-120°C, a second stage of medium temperature of 300°C-1600°C, and a reduction time of 6h-96h; Graphitizing the semi-finished graphene porous cloth to obtain a density of 0.1 g / cm 3 -0.8g / cm 3 , a graphene porous cloth with a porosity of 50%-90% and a thickness of 100μm-5000μm, wherein the temperature of the high temperature environment is 2000℃-3500℃, the heating rate is 1℃ / min-20℃ / min, and the insulation time is 30min-360min.
2. The preparation method according to claim 1, characterized in that: The step of shearing the graphene oxide film according to predetermined requirements to obtain graphene oxide film filaments, and shearing the graphene oxide film filaments to obtain graphene oxide short filaments, comprises: The graphene oxide is made into a graphene oxide film with a thickness of mainly 30-500 μm; The graphene oxide film is physically cut into graphene oxide film filaments with a width of 10 μm-1000 μm and a length of 5 cm-5000 cm; At least a portion of the graphene oxide membrane filaments are cut into graphene oxide short filaments with a length of 0.5 cm-5 cm.
3. The preparation method according to claim 1, characterized in that: The fusing and assembling of the graphene oxide membrane filaments and the graphene oxide short filaments to obtain the graphene oxide porous cloth comprises: Dispersing the graphene oxide membrane filaments and the graphene oxide short filaments in a mixture of alcohol and water in a volume ratio of 1:0.25-10; The graphene oxide membrane filaments and the graphene oxide short filaments in the mixed solution are overlapped in an orderly and / or disorderly manner by filtration or coating to form a graphene oxide porous cloth with an arbitrary shape and a pore size of 0.5 μm-100 μm.
4. The preparation method according to claim 1, characterized in that: The step of reducing the graphene oxide porous cloth at low to medium temperature to obtain a semi-finished graphene porous cloth comprises: The graphene oxide porous cloth is chemically reduced in a hydrazine hydrate solution with a concentration of 0.5% to 90% or hydrazine hydrate vapor with a concentration of 50% to 95%, or in an environment where it is immersed in a sodium ascorbate aqueous solution with a mass fraction of 1% to 50%, or a hydrobromic acid aqueous solution with a mass fraction of 1% to 48%, or a hydroiodic acid aqueous solution with a mass fraction of 1% to 58%, with the ambient temperature maintained at 60° C. to 95° C., wherein the reduction time is 2 h to 48 h; The reduced graphene porous cloth is treated in an inert gas at a medium temperature environment of 300° C. to 1600° C. to remove waste gas, thereby obtaining a semi-finished graphene porous cloth.
5. The preparation method according to claim 4, characterized in that: The reduced graphene porous cloth is treated in an inert gas at a medium temperature of 300° C. to 1600° C. to remove waste gas, thereby obtaining a semi-finished graphene porous cloth, comprising: The reduced graphene porous cloth is treated in argon or nitrogen at a low or medium temperature environment of 600° C. to 1600° C. to remove waste gas, thereby obtaining a semi-finished graphene porous cloth.
6. The preparation method according to claim 1, characterized in that: The semi-finished graphene porous cloth is graphitized to obtain a density of 0.1 g / cm 3 -0.8g / cm 3 , a graphene porous cloth with a porosity of 50%-90% and a thickness of 100μm-5000μm, comprising: The graphene oxide porous cloth after carbonization reduction treatment is placed in a heating device and graphitized in a high temperature environment to obtain a graphene porous cloth; wherein the temperature of the high temperature environment is 2000°C-3000°C or 3000°C-3300°C or 3300°C-3500°C; the heating rate is 1°C / min-2°C / min or 2°C / min-5°C / min or 5°C / min-10°C / min or 10°C / min-15°C / min; the insulation time is 30min-120min or 120min-360min.
7. The preparation method according to claim 1, characterized in that: The semi-finished graphene porous cloth is graphitized to obtain a density of 0.1 g / cm 3 -0.8g / cm 3 , a graphene porous cloth having a porosity of 50%-90% and a thickness of 100μm-5000μm, and also comprising: The graphene porous cloth is subjected to calendering treatment to obtain a flexible graphene porous cloth with a thickness of 10 μm-100 μm or 100 μm-500 μm, a density of 0.2 g / cm3-1 mg / cm3, and a porosity of 50%-90%.
8. The preparation method according to claim 7, characterized in that: The graphene porous cloth is subjected to calendering treatment to obtain a flexible graphene porous cloth having a thickness of 10 μm-100 μm or 100 μm-500 μm, a density of 0.2 g / cm3-1 mg / cm3, and a porosity of 50%-90%, comprising: The graphene porous cloth is subjected to static pressure treatment to obtain the flexible graphene porous cloth; wherein the static pressure includes segmented and graded static pressure, the pressure is 100 kPa-40 MPa and the static pressure time is 30 min-1440 min; or, The graphene porous cloth is subjected to rolling treatment to obtain the flexible graphene porous cloth, wherein the rolling pressure is 100 kPa-20 MPa, and the rolling speed is 0.1 m / min-5 m / min; or, The graphene porous cloth is subjected to static pressure treatment, wherein the static pressure includes segmented and graded static pressure, the pressure is 100 kPa-40 MPa and the static pressure time is 30 min-1440 min; The porous cloth after static pressing is rolled to obtain the flexible graphene porous cloth, wherein the rolling pressure is 100 kPa-20 MPa, and the rolling speed is 0.1 m / min-5 m / min.
9. The preparation method according to claim 8, characterized in that: The step of calendering the graphene porous cloth to obtain the flexible graphene porous cloth may further include: The graphene porous cloth is rolled by a double-roller machine to obtain the flexible graphene porous cloth with a thickness of 100 μm-500 μm, a density of 0.4 g / cm3-0.1 g / cm3, and a porosity of 60%-80%.
10. A porous cloth for a fuel cell gas diffusion layer, characterized in that: The porous cloth for fuel cell gas diffusion layer is produced by the production method described in any one of claims 1 to 9.
11. A fuel cell, characterized in that: It comprises the porous cloth for fuel cell gas diffusion layer as described in claim 10, which is applied to the fuel cell as a gas diffusion layer; the porous cloth for fuel cell gas diffusion layer is made by the preparation method described in any one of claims 1 to 9 above.
Citation Information
Patent Citations
Method for preparing novel lithium ion battery cathode materials
CN104485457A
Method for improving shearing force of layers of multi-direction long-yarn non-woven cloth
CN107630295A
Preparation method of high-heat conduction graphene heat-dissipating film
CN108793133A
Self-fused graphene oxide fiber paper and preparation method thereof
CN109295796A
Technical scheme for uniformly laying short shreds among layers of filament cloth
CN110406132A
